Facile growth of carbon nanotubes using microwave ovens: the emerging application of highly efficient domestic plasma reactors. Issue 12 (31st October 2019) - Liu, Yang; Guo, Naishun; Yin, Pengfei; Zhang, Chao
Abstract : Carbon nanotubes are obtained using a domestic microwave oven in a few seconds at room temperature and atmospheric pressure. Abstract : The facile growth of carbon nanotubes (CNTs) using microwave radiation reveals a new way for the cost-effective synthesis of CNTs for a wide range of applications. In this regard, domestic microwave ovens can be used as convenient plasma reactors to grow CNTs in a very fast, simple, energy-saving and solvent-free manner. The special heating mechanism of microwaves can not only accomplish the fast growth of high-density CNT brushes within tens of seconds, but also eliminate the need for a flammable gaseous carbon source and an expensive furnace. By carefully selecting the substrate and catalyst, low-temperature growth of CNTs can also be achieved on low-melting point organic polymers at atmospheric pressure. Highly localized heating near the catalyst nanoparticles was observed under microwave irradiation, and this phenomenon can be utilized to grow CNTs at desired locations on the substrate to fabricate CNT-based nanoelectronics in situ . Finally, the microwave growth of CNTs is highly adaptive to different carbon sources, substrates and catalysts, showing enormous potential to generate functionalized CNT-based composites for emerging advanced applications.